2016
DOI: 10.1002/ijc.30128
|View full text |Cite
|
Sign up to set email alerts
|

Clonal deleted latent membrane protein 1 variants of Epstein‐Barr virus are predominant in European extranodal NK/T lymphomas and disappear during successful treatment

Abstract: Extranodal natural killer/T-cell lymphomas (NK/TL), rare in Europe, are Epstein-Barr virus (EBV) associated lymphomas with poor outcomes. Here, we determined the virus type and analyzed the EBV latent membrane protein-1 (LMP1) gene sequence in NK/TL from French patients. Six clones of viral LMP1 were sequenced by Sanger technology in blood from 13 patients before treatment with an L-asparaginase based regimen and, for 8 of them, throughout the treatment. Blood LMP1 sequences from 21 patients without any known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Specific polymorphisms in two viral gene promoters Cp and Qp were found in nasopharyngeal carcinoma . A clonal LMP1 gene containing a 30 bp deletion (del30) was found in 46.1% of NK/T cell lymphomas and only in 4.8% of the controls, with much worse patient survival in those with this deletion . However, as shown in endemic Burkitt lymphoma, within a geographic region, different EBV genetic variations can coexist, such that specific gene variation associations with presentation or prognosis have been difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Specific polymorphisms in two viral gene promoters Cp and Qp were found in nasopharyngeal carcinoma . A clonal LMP1 gene containing a 30 bp deletion (del30) was found in 46.1% of NK/T cell lymphomas and only in 4.8% of the controls, with much worse patient survival in those with this deletion . However, as shown in endemic Burkitt lymphoma, within a geographic region, different EBV genetic variations can coexist, such that specific gene variation associations with presentation or prognosis have been difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Given that del30 strains have been currently detected in normal carriers [89] or in various EBV-associated diseases [90], and, because of a low prevalence of del30 strains in samples from Africa, North America, and Europe [8,91], it is generally admitted that LMP1 del30 may represent a geographic polymorphism rather than a diseaseassociated polymorphism [92]. In a study, we carried out in France in patients with NK/T lymphoma, we found a del30 EBV in 4/4 biopsies studied and in 46.1% of total blood samples analyzed, while in a control population, the deletion was present in 4.8% of cases [93]. Other deletions were also described, such as the rare C terminal 69 bp deletion reported to weakly activate the AP1 transcription factor [94], or the 15 bp deletion (aa 275-279) frequently encountered in Western Europe [93].…”
Section: Lmp1mentioning
confidence: 86%
“…EBV plays an important role in the lymphomagenesis of NKTL [ 27 ]. Latent membrane protein 1 (LMP1) is a major oncoprotein that is encoded by one of the EBV genes [ 28 ]. This protein contributes to the activation of the AKT pathway in EBV-infected lymphomas, which, in turn, affects cell survival, apoptosis, proliferation, and genomic instability via its downstream target proteins to cause cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%